Desenvolvimento de um inoculante liofilizado para a cultura de soja - Kniphoff, Carina de Lima (2013)
Nitrogen is a necessary nutrient for the growth and development of plants, especially leguminous plants such as soybeans having a high protein content in the grain. A large part of this nitrogen is obtained through the process of biological nitrogen fixation, where there is a symbiosis between bacteria of the Bradyrhizobium japonicum and Bradyrhizobium elkanii and plant. In this process, there is the formation of structures called nodules on the roots of plants, responsible for capturing atmospheric nitrogen and turning it into usable forms of nitrogen by the plant. Products containing these bacteria are called inoculants and their use is already well established for the planting of soybeans in Brazil but, the high mortality of this microorganism before the inoculation process, reduces the effectiveness and only allows inoculation right before planting. Therefore, the objective of this study was to develop an inoculant with freeze-dried bacteria, which are more resistant to the drying process that occurs during inoculation, allowing the seed to be inoculation a few days before planting, facilitating the work of farmers. SEMIA 5079 and SEMIA 5080 of B. japonicum were lyophilized in the presence of glycerol as cellular protectors (10%), sucrose (20%), peptone (10%) and bacteriological gelatin (5%) and analysis was performed of cell viability. To determine the shelf life, analysis was performed of cell viability of lyophilized inoculant containing 20% sucrose compared with the sample without the addition of protectors over a period of three months. Analysis of cell viability on the seed was performed after inoculation and 24, 48 , 72 and 96 hours after comparing the lyophilized inoculant with 20% liquid sucrose with commercial standard. To determine the production costs we considered lyophilized product yield, cost and initial investment savings in transportation. The use of sucrose was more efficient before others and shelf life retained high cell concentration (2,24 x 1010 CFU/g) at three months after lyophilization, whereas the mortality of the inoculant lyophilized without addition was 100%. The viability of bacteria on the seed was greater for the lyophilized inoculant, keeping 1,14 x 105 CFU/seed for 96 hours compared to 1,7 x 104 CFU/seed for liquid inoculant. Despite the reduction in four-fold the cost of transportation to the inoculant lyophilized there is need for initial investment for equipment acquisition of approximately R$390.000,00. From these data, we conclude that the investment of an industry for producing a lyophilized inoculant for soybean is only feasible if the shelf life is greater than 18 months and it is necessary to test the viability for a longer period.